1987
DOI: 10.1080/02681218780000451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a test to detect circulatingAspergillus fumigatusantigen in a survey of immunocompromised patients with proven or suspected invasive disease

Abstract: An ELISA for the detection and measurement ofAspergillus antigenaemia has been developed and evaluated by examining sera submitted over a 12-month period from immunocompromised patients with a likelihood of invasive aspergillosis. Results from proven cases ofinvasive aspergillosis confirmed at post-mortem and specimens from individuals with suspected disease showed that tests on single serum samples were often negative. Multiple specimens from the same patient greatly increased the frequency of deteclion. Repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 27 publications
(30 reference statements)
0
33
0
Order By: Relevance
“…Since the first report by Reiss and Lehmann, 12 several methods have been used to detect Aspergillus antigens in biological specimens (sera and urine) of patients with invasive aspergillosis. [13][14][15][16][17][18][19][20][21] Among all Aspergillus cellular products, galactomannan has been studied the most extensively and it has been shown to be …”
Section: Discussionmentioning
confidence: 99%
“…Since the first report by Reiss and Lehmann, 12 several methods have been used to detect Aspergillus antigens in biological specimens (sera and urine) of patients with invasive aspergillosis. [13][14][15][16][17][18][19][20][21] Among all Aspergillus cellular products, galactomannan has been studied the most extensively and it has been shown to be …”
Section: Discussionmentioning
confidence: 99%
“…Studies with purified antigens would be of value in understanding both humoral and cell-mediated arms of immune response in aspergillosis. In contrast, the lymphokines and the cellmediated mechanisms by which T cells participate in the regulation of IgE synthesis and eosinophil activation and differentiation in certain other allergic diseases have been well documented (99,231 (6,124,190 (80,82,115,132,172,194,197,249 (74,115,122,197,248,250). On the other hand, in IA, galactomannan and glycoproteins are the major circulating antigens (25,50,179 (101,114,228,229).…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…When the 250,000-molecular-weight antigen was used in ELISA to test the sera from patients with aspergilloma, 13 Immunoblotting. Several studies have shown that glycoprotein antigens, a major constituent of both the mycelium and the culture filtrate of A. fumigatus, have high immunological reactivity (23,74,115,197,246,250). These antigens can be characterized by their molecular size, isoelectric points, ability to bind to ConA or other lectins, and enzymatic activity.…”
Section: Humoral Immune Responsementioning
confidence: 99%
See 2 more Smart Citations